2021
DOI: 10.1097/htr.0000000000000671
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare Providers' Self-Reported Pediatric Mild Traumatic Brain Injury Diagnosis, Prognosis, and Management Practices: Findings From the 2019 DocStyles Survey

Abstract: Prevention evidence-based guideline on pediatric mild traumatic brain injury, this article presents results from the 2019 DocStyles survey. Study Design: Cross-sectional, web-based survey of 653 healthcare providers. Results: Most healthcare providers reported adhering to the recommendations regarding the use of computed tomography and providing education and reassurance to patients and their families. However, less than half reported routinely examining their patients with mild traumatic brain injury (mTBI) u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…Our findings suggest that implementing a relatively simple clinical pathway in the ED can promote outpatient follow-up, in accordance with existing practice guidelines [ 6 – 8 ], while enabling physicians to care for children with concussion more efficiently. By standardizing the guidance offered to patients and families, the clinical pathway also likely helps to reduce practice variation in the acute care of pediatric concussion [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings suggest that implementing a relatively simple clinical pathway in the ED can promote outpatient follow-up, in accordance with existing practice guidelines [ 6 – 8 ], while enabling physicians to care for children with concussion more efficiently. By standardizing the guidance offered to patients and families, the clinical pathway also likely helps to reduce practice variation in the acute care of pediatric concussion [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical practice guidelines for acute care of concussion recommend assessment of risk factors for persistent post-concussive symptoms, education about concussion self-management and return to school and sport, and referral for follow-up [ 6 – 8 ]. However, guideline implementation is inconsistent, and significant practice variation persists [ 9 , 10 ]. This failure of knowledge translation likely occurs because practice guidelines are seldom translated into clinical pathways [ 11 , 12 ] and because pathway implementation typically relies on passive dissemination rather than active, planned interventions [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Knowledge and misconceptions about mTBI have been assessed in other populations as well. Those studies have revealed that misconceptions regarding mTBI symptoms by pediatric primary care,14 emergency medicine providers,6 and among experienced and fully trained US Army behavioral health providers11 are widespread. Surveys of youth sports coaches have revealed that many have misconceptions about mTBI, which can be improved with education 20,21…”
Section: Discussionmentioning
confidence: 99%
“…This study is the first to assess US military healthcare clinicians' self-reported knowledge, practices, training preferences, confidence in treatment and management, and utilization of current resources related to caring for those experiencing concussion. This work expands the body of literature investigating provider misconceptions regarding diagnosis and management of TBI 14 and builds on this literature by examining barriers to concussion management and by providing insight into the types of additional resources that may be needed to ensure clinicians are providing evidence-based care.…”
mentioning
confidence: 97%